(untitled) (Aporte Santiaguino, 2025)
Several issues related to the performance of tailings dams in mining companies are currently being discussed. Conventional construction requires a considerable area and must not affect the local ecosystem. Building a tailings dam near a population or water source would cause significant environmental, economic, and social damage in the event of a dam failure. Addressing this issue, we propose analyzing filtered tailings and thereby forming the dam, which would be a mixture of the Esperanza mine waste in a ratio of (3 tailings + 1 mine waste) and forming the tailings basin, which would consist solely of filtered tailings. In this article, we will present the procedures for analyzing filtered tailings in the construction of the mining dam, as well as pilot tests using a filter press to ensure optimal moisture content for the dam’s construction and disposal in the basin. With the physical stability analysis we guarantee safety for statistic conditions greater than 1.5 and pseudo-static conditions greater than 1.0 according to the regulations of the Ministry of Energy and Mines.